E-3: JUDICIAL ACTIVISM IN PAKISTAN: THE IMPACT OF MODERN DEVICES ON EVIDENCE AND CERDIBILITY - Saeed, Aliya; Dastagir, Ghulam; Ali, Syed Fahad (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
In contemporary legal systems worldwide, the incorporation of modern devices and techniques as evidence has become an essential component, reflecting a paradigm shift towards embracing technological advancements in the pursuit of justice. This paper delves into the nuanced approach adopted by Pakistani courts concerning the admissibility of modern devices and techniques as evidence. In examining the jurisprudence of Pakistani courts, it becomes evident that they recognize the significance of modern evidence-gathering methods. Through an analysis of case law and legal principles, this study sheds light on the evolving attitude of Pakistani courts towards incorporating evidence obtained through modern devices such as DNA profiling, CCTV footage, and electronic communications. The paper discusses landmark cases where Pakistani courts have grappled with the admissibility of evidence procured through modern techniques, outlining the criteria used to assess its reliability and relevance. It explores the legal framework governing the admission of such evidence, including the provisions of the Qanun-e-Shahadat Order, 1984, and relevant judicial precedents. Furthermore, the study examines the challenges faced by Pakistani courts in effectively integrating modern evidence into the legal system. Issues such as chain of custody, authentication, and the need for corroborating evidence are explored within the context of contemporary legal practice in Pakistan. Ultimately, this paper offers insights into the evolving landscape of evidence law in Pakistan, highlighting the growing importance of embracing modern devices and techniques in the pursuit of justice. It underscores the need for the judiciary to adapt to technological advancements while ensuring adherence to principles of fairness, reliability, and procedural integrity.